Histopathology of skin melanocytic lesions - Pock, Lumír; Skálová, Alena (Ceskoslovenska patologie, 2024)
Melanocytic lesions are instable tumors, the genome of which and its changes determinate their morphology and biological properties. Intermediate lesions share histomorphological features of both, nevi and melanoma. Melanocytomas represent a group of them separated on the basis of recent molecular-biological studies. The article summarizes benign, intermediate, malignant and combined melanocytic skin lesions and offers practical recommendations for diagnosis.
Keywords: practical recommendations for diagnosis; Humans; Skin Neoplasms; dermoscopy-histopathology correlations; nádory kůže; classification; melanom; genetic alterations; melanocytomas; intermediate lesions; pigmentový névus; Melanoma; Nevus, Pigmented; lidé; melanocytic lesions; histopathology